Positive electrode sheet and method for manufacturing the same

CN117673254BActive Publication Date: 2026-10-16NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311810320.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-16
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

析锂现象不仅会使电池性能下降,循环寿命大幅缩短,还会限制电池的快充容量,并有可能引起燃烧、爆炸等灾难性后果

Benefits of technology

[0004] One objective of this application is to provide a positive electrode sheet and a method for preparing the same, which can improve the problem of lithium deposition in the negative electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117673254B_ABST
    Figure CN117673254B_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode tab and a preparation method thereof. The positive electrode tab comprises a current collector and an active material layer arranged on the surface of the current collector. The active material layer comprises a coated area and a non-coated area connected with each other, the coated area comprises a non-active material, and the non-active material can hinder the transmission of metal ions. In the thickness direction of the positive electrode tab, the coated area is located on at least one side of the non-coated area, and the content of the non-active material in the coated area decreases in the direction from the coated area to the non-coated area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage devices, and in particular to a positive electrode sheet and its preparation method. Background Technology

[0002] In recent years, rechargeable batteries (also known as secondary batteries) have been increasingly used in high-tech, high-intensity, and high-requirement fields such as consumer goods, new energy vehicles, large-scale energy storage, aerospace, shipbuilding, and heavy machinery, and are even used as primary power and energy supply equipment in these fields. Among the various secondary batteries developed, lithium-ion secondary batteries have attracted widespread attention due to their superior performance.

[0003] During cycling, lithium-ion rechargeable batteries are prone to lithium plating on the negative electrode. Lithium plating not only degrades battery performance and significantly shortens cycle life, but also limits the battery's fast-charging capacity and may cause catastrophic consequences such as combustion and explosion. Summary of the Invention

[0004] One objective of this application is to provide a positive electrode sheet and a method for preparing the same, which can improve the problem of lithium deposition in the negative electrode sheet.

[0005] A first aspect of this application provides a positive electrode sheet, including a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes a coated region and an uncoated region connected together. The coated region includes an inactive material that can hinder the transport of metal ions. Viewed along the thickness direction of the positive electrode sheet, the coated region is located on at least one side of the uncoated region. Along the direction from the coated region to the uncoated region, the content of the inactive material in the coated region decreases.

[0006] The positive electrode provided in this application has an inactive material disposed in the coating area of ​​the active material layer, which reduces the lithium ion transport rate in the coating area and reduces the risk of lithium plating in the negative electrode area opposite to the coating area; and the content of inactive material in the coating area decreases along the direction from the coating area to the uncoated area, reducing the risk of lithium plating shifting from the edge or corner to the main body of the negative electrode at the junction of the coating area and the uncoated area due to abrupt changes in kinetics.

[0007] In some embodiments, the inactive substance is at least one of UV adhesive and PVDF.

[0008] In some embodiments, the UV adhesive is formed by curing a UV adhesive liquid, which includes a resin and a photoinitiator.

[0009] In some embodiments, the resin comprises at least one of a polyacrylate prepolymer or a derivative thereof, and the photoinitiator comprises at least one of an acylphosphine oxide or a thioxanthone.

[0010] In some embodiments, the inactive substance comprises at least one element selected from P, S, or F.

[0011] In some embodiments, the coating area is configured to correspond to the edge of the active material layer. The coating area includes a first end and a second end opposite to each other. The first end is in contact with the uncoated area, and the second end is disposed away from the uncoated area. The mass percentage content of P or S at the first end is 0.01% to 0.04% more than the mass percentage content of P or S in the uncoated area, and the mass percentage content of P or S at the second end is 0.05% to 0.1% more than the mass percentage content of P or S in the uncoated area. The mass percentage content of P or S at the first end is less than the mass percentage content of P or S at the second end.

[0012] In some embodiments, the coating area is configured to correspond to the edge of the active material layer. The coating area includes a first end and a second end opposite to each other. The first end is in contact with the uncoated area, and the second end is disposed away from the uncoated area. The mass percentage content of F at the first end is 0.2% to 0.4% higher than the mass percentage content of F in the uncoated area, and the mass percentage content of F at the second end is 0.5% to 1% higher than the mass percentage content of F in the uncoated area. The mass percentage content of F at the first end is less than the mass percentage content of F at the second end.

[0013] In some embodiments, the coating area is configured to correspond to the bend in the positive electrode sheet after winding, and the content of inactive material in the coating area decreases along the direction from the center of the coating area to the edge of the coating area.

[0014] In some embodiments, the coated area is configured to correspond to the bend of the positive electrode sheet after winding, and the mass percentage content of F at the center of the coated area is 0.5% to 1% higher than the mass percentage content of F in the uncoated area, and the mass percentage content of F at the edge of the coated area is 0.2% to 0.4% higher than the mass percentage content of F in the uncoated area.

[0015] In some embodiments, the coating area is configured to correspond to the bend after the positive electrode sheet is wound, the mass percentage content of P or S at the center of the coating area is 0.05% to 0.1% higher than the mass percentage content of P or S in the uncoated area, the mass percentage content of P or S at the edge of the coating area is 0.01% to 0.04% higher than the mass percentage content of P or S in the uncoated area, and the mass percentage content of P or S at the edge of the coating area is less than the mass percentage content of P or S at the center of the coating area.

[0016] In some embodiments, the coating area is configured to correspond to the edge of the active material layer, and the width of the coating area is 2 to 10 mm.

[0017] A second aspect of this application provides a method for preparing a positive electrode sheet, comprising the following steps:

[0018] An active substance slurry is coated onto the surface of the current collector to form the active substance layer;

[0019] An inactive substance slurry is coated onto the surface of the active substance layer to form the coating area, wherein, when the coating area is configured to correspond to the edge of the active substance layer, the coating weight of the inactive substance slurry decreases along the direction from the coating area to the uncoated area; and when the coating area is configured to correspond to the bend of the positive electrode sheet after winding, the coating weight of the inactive substance slurry decreases along the direction from the center of the coating area to the edge of the coating area.

[0020] In some embodiments, the step of "coating the surface of the active material layer with an inactive substance slurry to form a coating area" includes:

[0021] To create a print image file, the maximum spraying amount is set to the maximum content of inactive substances in the coated area. The relative contrast value of the image corresponding to the maximum spraying amount is 100%. Based on the maximum spraying amount, the relative contrast value of the image is set to decrease from the second end to the first end of the coated area or from the center to the edge of the coated area. The color of the print image file changes from dark to light along the direction from the coated area to the uncoated area or from dark to light along the direction from the center to the edge of the coated area.

[0022] Import the inkjet image file into the inkjet printing equipment and set the spray volume when the relative contrast value is 100%. The inkjet printing equipment will set the spray ratio according to the relative contrast value ratio of the image file and spray the pattern of the corresponding size according to the size of the image file.

[0023] The nozzle is controlled to spray the inactive substance slurry onto the surface of the active substance layer at a target spray volume to form a coating area.

[0024] In some embodiments, the step of "coating the surface of the active material layer with an inactive substance slurry to form a coating area" includes:

[0025] To create the engraved pattern, the maximum coating amount is determined by the maximum content of inactive substances in the coating area. The relative contrast value of the image corresponding to the maximum coating amount is 100%. Based on the maximum coating amount, the relative contrast value of the image is set to decrease from the second end to the first end of the coating area or from the center to the edge of the coating area. The color of the engraved pattern changes from dark to light along the direction from the coating area to the uncoated area or from dark to light along the direction from the center to the edge of the coating area. The corresponding engraved pattern size is set according to the required coating width.

[0026] The engraved pattern is imported into the gravure engraving machine, which will engrave halftone pits of different densities according to the relative contrast ratio of the engraved pattern to correspond to different coating amounts. The gravure engraving machine engraves the corresponding coating area size according to the size of the image file to produce the gravure roller.

[0027] A gravure roller is used to apply an inactive substance slurry onto the surface of the active substance layer to form a coating area. Attached Figure Description

[0028] Figure 1 This is a view along the thickness direction of the unfolded positive electrode sheet provided in one embodiment of this application.

[0029] Figure 2 This is a view of the positive electrode sheet provided in one embodiment of this application, viewed along the width direction.

[0030] Figure 3 This is a view along the thickness direction of the unfolded positive electrode sheet provided in another embodiment of this application.

[0031] Figure 4 for Figure 3 A cross-sectional view of the positive electrode along its length.

[0032] Figure 5 This is a view of the positive electrode sheet along the thickness direction, provided for yet another embodiment of this application.

[0033] Figure 6 This is a view of the positive electrode sheet along the thickness direction, provided for yet another embodiment of this application.

[0034] Explanation of main component symbols

[0035] Positive electrode 100

[0036] Current collector 10

[0037] Active material layer 20

[0038] Earl 30

[0039] Uncoated area 21

[0040] First coating area 22

[0041] Second coating area 23

[0042] First end 22a, 23a

[0043] Second end 22b, 23b

[0044] Third coating area 24

[0045] Width direction W

[0046] Length direction L

[0047] Thickness direction T

[0048] Edges 20a, 20b Detailed Implementation

[0049] The technical solutions in the embodiments of this application are described clearly and in detail below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the specification of this application is for the purpose of describing particular embodiments only and is not intended to limit this application.

[0050] Embodiments of this application will now be described in detail. However, this application may be embodied in many different forms and should not be construed as limited to the exemplary embodiments set forth herein. Rather, these exemplary embodiments are provided to provide a thorough and detailed understanding of this application to those skilled in the art.

[0051] As used herein, the terms “and / or” and “with and / or” include any and all combinations of one or more of the associated enumerated items. Additionally, it should be understood that when element A is referred to as “connecting” element B, element A may be directly connected to element B, or there may be an intermediate element C and element A and element B may be indirectly connected to each other.

[0052] Furthermore, when describing embodiments of this application, the word "may" refers to "one or more embodiments of this application".

[0053] The technical terms used herein are for the purpose of describing particular embodiments and are not intended to limit the application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. It should be further understood that the term "comprising," as used in this specification, means the presence of the described features, values, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, values, steps, operations, elements, components, and / or combinations thereof.

[0054] One embodiment of this application provides a secondary battery, including a housing and an electrode assembly and an electrolyte housed within the housing. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The positive electrode, separator, and negative electrode are alternately stacked to form a laminated structure. In other embodiments, the positive electrode, separator, and negative electrode are stacked and then wound to form a wound structure. The wound structure has a flat portion and a curved portion, wherein the flat portion is the straight extension of the positive electrode, negative electrode, or separator after winding, and the curved portion is the bent extension of the positive electrode, negative electrode, or separator after winding.

[0055] Please see Figure 1 and Figure 2 The positive electrode 100 includes a current collector 10, an active material layer 20 located on the surface of the current collector 10, and a tab 30 connected to the current collector 10. The active material layer 20 may be located on one surface or two opposite surfaces of the current collector 10. The tab 30 (see...) Figure 5 The tab 30 protrudes from the current collector 10 along the width direction W of the positive electrode 100. The width direction of the positive electrode 100 refers to the direction of the short side of the positive electrode 100. The tab 30 and the current collector 10 can be integrally formed or separately formed.

[0056] The active material layer 20 is generally sheet-like and includes an interconnected uncoated region 21 and a coated region. The coated region is formed by coating the surface of the active material layer 20 with an inactive material slurry, while the uncoated region 21 is not coated with the inactive material slurry. In this embodiment, the coated region includes a first coated region 22. Viewed along the thickness direction T of the positive electrode sheet 100, the first coated region 22 is located on both sides of the uncoated region 21 in the width direction W, and the first coated region 22 is configured to correspond to the edge 20a of the active material layer 20 in the width direction W. In this application, the correspondence between the first coated region 22 and the edge 20a means that the first coated region 22 covers the edge 20a. In other embodiments, the first coated region 22 is located on one side of the uncoated region 21 in the width direction W.

[0057] Both the uncoated region 21 and the first coated region 22 include a positive electrode active material, which may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, or lithium cobalt phosphate. Both the uncoated region 21 and the first coated region 22 may also include a conductive agent and a binder. The conductive agent may include at least one of conductive carbon black, carbon nanotubes, carbon fibers, or graphene, and the binder may include at least one of styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, or sodium carboxymethyl cellulose.

[0058] The first coating region 22 also includes an inactive material that hinders the transport of metal ions. By configuring the inactive material, the kinetics of the first coating region 22 are reduced, slowing down the rate at which metal ions (e.g., lithium ions) are extracted from the first coating region 22 during charging. This reduces the risk of lithium plating in the negative electrode area opposite the first coating region 22, thereby improving the cycle life of the secondary battery. In some embodiments, the uncoated region 21 also includes an inactive material, and the content of the inactive material in the coated region is greater than the content of the inactive material in the uncoated region 21.

[0059] Along the direction from the first coated area 22 to the uncoated area 21, that is, along Figure 1In the width direction W or its opposite direction, the content of inactive material in the first coating region 22 decreases. The first coating region 22 includes a first end 22a and a second end 22b opposite to each other in the width direction W. The first end 22a is connected to the uncoated region 21, and the second end 22b is disposed away from the uncoated region 21 and coincides with the edge 20a of the active material layer 20. The content of inactive material at the first end 22a is less than that at the second end 22b. In some embodiments, the content of inactive material at the first end 22a is the minimum and the content of inactive material at the second end 22b is the maximum in the width direction W. By configuring the inactive material with a decreasing content along the direction from the first coating region 22 to the uncoated region 21, the risk of lithium plating due to abrupt changes in kinetics at the negative electrode opposite the boundary between the first coating region 22 and the uncoated region 21 can be reduced.

[0060] The inactive material is at least one of photosensitive adhesive (UV adhesive) and polyvinylidene fluoride (PVDF). The UV adhesive is formed by curing a UV adhesive solution. The UV adhesive solution includes a resin and a photoinitiator. The resin includes at least one of a polyacrylate prepolymer or a derivative thereof, and the photoinitiator includes at least one of an acylphosphine oxide or a thioxanthone. The photoinitiator contains sulfur (S) or phosphorus (P) elements, and the content of the inactive material can be limited by limiting the content of S or P elements. When the inactive material includes the UV adhesive, the content of S or P elements decreases along the direction from the first coated area 22 to the uncoated area 21. The PVDF is formed by curing a PVDF adhesive solution. The PVDF adhesive solution is formed by dissolving PVDF in a solvent (e.g., N-methylpyrrolidone). The PVDF contains sulfur (F), and the content of the inactive material can be limited by limiting the content of F elements. When the inactive material includes PVDF, the content of F elements decreases along the direction from the first coated area 22 to the uncoated area 21.

[0061] In some embodiments, when the inactive material includes a UV adhesive, the mass percentage content of P or S at the first end 22a is 0.01% to 0.04% higher than the mass percentage content of P or S in the uncoated region 21, and the mass percentage content of P or S at the second end 22b is 0.05% to 0.1% higher than the mass percentage content of P or S in the uncoated region 21, and the mass percentage content of P or S at the first end 22a is less than the mass percentage content of P or S at the second end 22b. When the inactive material includes PVDF, the mass percentage content of F at the first end 22a is 0.2% to 0.4% higher than the mass percentage content of F in the uncoated region 21, and the mass percentage content of F at the second end 22b is 0.5% to 1% higher than the mass percentage content of F in the uncoated region 21, and the mass percentage content of F at the first end 22a is less than the mass percentage content of F at the second end 22b. By configuring the inactive material within the above-described content ranges, the lithium plating problem can be significantly improved.

[0062] In some embodiments, the content of inactive material gradually decreases along the direction from the first coated area 22 to the uncoated area 21. Along the direction from the first coated area 22 to the uncoated area 21, starting from the edge 20a of the active material layer 20, a point is selected every 1000 μm and recorded as "1, 2, 3, 4…X". The point at the second end 22b is recorded as "1", and the point at the first end 22a is recorded as "X". The content of P, S, or F elements at each point is recorded as X. x Where X1 > X2 > X3 > X4 ... > X x ≥0. In some embodiments, the width of the first coating area 22 along the width direction W is 2 to 10 mm. If the width of the first coating area 22 is too large, the capacity loss of the secondary battery will be too large; if the width of the first coating area 22 is too small, the effect of the first coating area 22 in suppressing lithium plating will be relatively limited.

[0063] Please see Figure 3 and Figure 4 In some embodiments, the coating area includes a second coating area 23. Viewed along the thickness direction T, the second coating area 23 is located on both sides of the uncoated area 21 in the length direction L of the positive electrode 100, and the second coating area 23 is configured to correspond to the edge 20b of the active material layer 20 in the length direction L. In this application, the length direction L of the positive electrode 100 refers to the direction of the long side of the positive electrode 100, and the correspondence between the second coating area 23 and the edge 20b means that the second coating area 23 covers the edge 20b. In other embodiments, the second coating area 23 is located on both sides of the uncoated area 21 in the length direction L.

[0064] The second coating region 23 also includes the aforementioned inactive material to reduce the risk of lithium plating in the region of the negative electrode opposite to the second coating region 23. Along the direction from the second coating region 23 to the uncoated region 21, i.e. along... Figure 3 In the length direction L or its opposite direction, the content of S, P, or F elements in the second coating region 23 decreases. The second coating region 23 includes a first end 23a and a second end 23b opposite each other in the length direction L. The first end 23a is connected to the uncoated region 21, and the second end 23b is disposed away from the uncoated region 21 and coincides with the edge 20b. In some embodiments, in the length direction L, the content of inactive substances is minimal at the first end 23a and maximal at the second end 23b.

[0065] In some embodiments, the mass percentage content of P or S at the first end 23a is 0.01% to 0.04% higher than the mass percentage content of P or S in the uncoated region 21, and the mass percentage content of P or S at the second end 23b is 0.05% to 0.1% higher than the mass percentage content of P or S in the uncoated region 21, and the mass percentage content of P or S at the first end 23a is less than the mass percentage content at the second end 23b; and / or the mass percentage content of F at the first end 23a is 0.2% to 0.4% higher than the mass percentage content of F in the uncoated region 21, and the mass percentage content of F at the second end 23b is 0.5% to 1% higher than the mass percentage content of F in the uncoated region 21, and the mass percentage content of F at the first end 23a is less than the mass percentage content of F at the second end 23b. In some embodiments, the mass percentage content of P, S, or F in the second coated region 23 gradually decreases along the direction from the second coated region 23 to the uncoated region 21.

[0066] In some embodiments, the width of the second coating area 23 along the length direction L is 2 to 10 mm, so that the second coating area 23 plays a significant role in suppressing lithium plating and has little impact on the capacity of the secondary battery.

[0067] Please see Figure 5 In some embodiments, the coating area includes a first coating area 22 and a second coating area 23, and when viewed along the thickness direction T, the uncoated area 21 is located within the coating area.

[0068] Please see Figure 6 In some embodiments, the coating area includes a third coating area 24. Viewed along the thickness direction T, the third coating area 24 is located within the uncoated area 21, and is configured to correspond to the curved portion of the positive electrode sheet 100 after winding. In this application, "the third coating area 24 corresponds to the curved portion after winding" means that the third coating area 24 overlaps with the curved portion after winding. The number of third coating areas 24 can be set according to actual needs. Figure 5 The case where there are six third coating areas 24 is shown. Along the length direction L, the multiple third coating areas 24 divide the uncoated area 21 into multiple parts. When the positive electrode sheet 100 is used to form an electrode assembly with a wound structure, the third coating areas 24 are located in the curved portion of the wound structure, and the uncoated area 21 is located in the flat portion of the wound structure.

[0069] In some embodiments, both the uncoated region 21 and the third coated region 24 include a positive electrode active material, a conductive agent, and a binder. The third coated region 24 also includes the aforementioned inactive material to reduce the risk of lithium plating in the region of the negative electrode opposite to the third coated region 24. Along the direction from the center of the third coated region 24 to its edge, i.e. along... Figure 3In the length direction L or its opposite direction, the content of inactive substances in the third coating area 24 decreases. The center of the third coating area 24 refers to the central position of the third coating area 24 in the length direction L, and the edge of the third coating area 24 refers to the two edges of the third coating area 24 in the length direction L. The content of inactive substances in the center of the third coating area 24 is greater than the content of inactive substances in the edges of the third coating area 24.

[0070] In some embodiments, the content of S, P, or F elements in the third coating region 24 decreases along the direction from the center to the edge of the third coating region 24. In some embodiments, the mass percentage content of P or S at the edge of the third coating region 24 is 0.01% to 0.04% higher than the mass percentage content of P or S in the uncoated region 21, the content of P or S at the center of the third coating region 24 is 0.05% to 0.1% higher than the mass percentage content of P or S in the uncoated region 21, and the mass percentage content of P or S at the edge of the third coating region 24 is lower than the mass percentage content of P or S at the center; and / or the mass percentage content of F at the edge of the third coating region 24 is 0.2% to 0.4% higher than the mass percentage content of F in the uncoated region 21, the mass percentage content of F at the center of the third coating region 24 is 0.5% to 1% higher than the mass percentage content of F in the uncoated region 21, and the mass percentage content of F at the edge of the third coating region 24 is lower than the mass percentage content of F at the center.

[0071] In some embodiments, the content of S, P, or F elements in the third coating region 24 gradually decreases along the direction from the center to the edge of the third coating region 24. Along the direction from the center to the edge of the third coating region 24, starting from the center of the third coating region 24, a point is selected every 1000 μm and recorded as "1, 2, 3, 4...Y", where the point at the center of the third coating region 24 is recorded as "1", and the point at the edge of the third coating region 24 is recorded as "Y". The content of P, S, or F elements at each point is recorded as Y. Y Among them, Y1 > Y2 > Y3 > Y4 ... > Y Y ≥0.

[0072] In some embodiments, along the length direction L, the width of the third coating region 24 extending beyond the curved portion of the positive electrode sheet 100 after winding is 2 to 10 mm, so that the third coating region 24 plays a sufficiently significant role in suppressing lithium plating and has a small impact on the capacity of the secondary battery.

[0073] In some embodiments, the porosity of the coated area is 10% to 20%, thus preserving a certain lithium-ion diffusion rate and further reducing the risk of lithium plating without affecting the charge / discharge rate.

[0074] In some embodiments, if the uncoated area 21 does not contain the aforementioned inactive substances, then the content of inactive substances in the coated area is the amount of inactive substances in the coated area that is greater than that in the uncoated area 21.

[0075] The current collector 10 can be any known current collector, such as aluminum foil, aluminum alloy foil, or composite current collector.

[0076] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative current collector can be any known current collector, such as copper foil, copper alloy foil, or composite current collector. The negative active material layer includes a negative active material, which may include at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon, or silicon oxide. The negative active material layer may also include a conductive agent and a binder. The conductive agent may include at least one of conductive carbon black, carbon nanotubes, carbon fibers, or graphene, and the binder may include at least one of styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, or sodium carboxymethyl cellulose.

[0077] The release liner can be any known release liner. For example, the release liner can be a film selected from one or more materials selected from polyethylene, polypropylene, nonwoven fabric, and polyfiber.

[0078] The electrolyte can be any known electrolyte. For example, the electrolyte is selected from solutions containing one or more organic carbonate esters selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate or methyl ethyl carbonate as solvents, and containing one or more lithium salts selected from LiPF6, LiBF4, LiBOB, LiAsF6, Li(CF3SO2)2N or LiCF3SO3 as solutes.

[0079] The casing can be any known casing suitable for secondary batteries. For example, the casing can be a packaging bag made by encapsulating with a sealing film, such as aluminum-plastic film, steel-plastic film, etc.; or, the casing can be a metal casing, such as a steel casing, aluminum casing, etc.

[0080] An embodiment of this application also provides a method for preparing a positive electrode sheet, comprising the following steps: (a) mixing a positive electrode active material, a binder, and a conductive agent in a mass ratio of 96-98%:1%-2%:1-2% and stirring the mixture evenly in a solvent to form an active material slurry; (b) coating the active material slurry onto the surface of a current collector to form an active material layer; (c) coating an inactive material slurry onto the surface of the active material layer to form a coating area, wherein, when the coating area is configured to correspond to the edge of the active material layer, the coating weight of the inactive material slurry decreases along the direction from the coating area to the uncoated area; when the coating area is configured to correspond to the curved portion of the positive electrode sheet after winding, the coating weight of the inactive material slurry decreases along the direction from the center of the coating area to the edge of the coating area.

[0081] The solvent in step (a) may include at least one of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran.

[0082] In step (c), the inactive substance slurry can be at least one of UV adhesive and PVDF adhesive. After the inactive substance slurry is coated on the surface of the active substance layer, at least a portion of the inactive substance slurry penetrates into the active substance layer to form a coated area. The portion of the active substance layer not coated with the inactive substance slurry is considered the uncoated area of ​​the active substance layer.

[0083] In some embodiments, in step (c), an inactive substance paste is coated onto the surface of the active substance layer using inkjet printing with a printing setup. The printing equipment includes a plurality of printheads arranged in an array. Step (c) includes the following steps:

[0084] To create a print image file, the maximum spraying amount is determined by the maximum content of inactive material in the coated area. The relative contrast value of the image corresponding to the maximum spraying amount is 100%. Based on the maximum spraying amount, the relative contrast value of the image is set to decrease from the second end to the first end of the coated area or from the center to the edge of the coated area. The color of the print image file changes from dark to light along the direction from the coated area to the uncoated area or from dark to light along the direction from the center to the edge of the coated area. The size of the image corresponds to the size of the spraying.

[0085] Import the inkjet image file into the inkjet printing equipment and set the spraying amount when the relative contrast value is 100%. The inkjet printing equipment will set the spraying ratio according to the relative contrast value ratio of the image file and spray the corresponding size of the coating width according to the size of the image file.

[0086] The nozzle is controlled to spray the inactive substance slurry onto the surface of the active substance layer at a target spray volume to form a coating area.

[0087] In another embodiment, in step (c), the inactive substance paste is coated onto the surface of the active substance layer using gravure printing. Step (c) includes the following steps:

[0088] To create the engraved pattern, the maximum coating amount is determined by the maximum content of inactive substances in the coating area. The relative contrast value of the image corresponding to the maximum coating amount is 100%. Based on the maximum coating amount, the relative contrast value of the image is set to decrease from the second end to the first end of the coating area or from the center to the edge of the coating area. The color of the engraved pattern changes from dark to light along the direction from the coating area to the uncoated area or from dark to light along the direction from the center to the edge of the coating area. The corresponding engraved pattern size is set according to the required coating width.

[0089] The engraved pattern is imported into the gravure engraving machine, which engraves halftone pits of different densities according to the relative contrast ratio of the engraved pattern to correspond to different coating amounts; the gravure engraving machine engraves the corresponding coating area size according to the size of the image file; thus producing the gravure roller.

[0090] A gravure roller is used to apply an inactive substance slurry onto the surface of the active substance layer to form a coating area.

[0091] In other embodiments, the inactive substance slurry can be coated onto the surface of the active substance layer by means of flatbed screen printing, roller screen printing, slot extrusion, offset printing, etc.

[0092] One embodiment of this application provides an electronic device including the aforementioned secondary battery. The electronic device can be a consumer electronics device, a drone, a power tool, an energy storage device, or an electric vehicle, etc.

[0093] The following are some specific embodiments and comparative examples to better illustrate this application, wherein a lithium-ion battery is used as an example.

[0094] Example 1

[0095] Preparation of the positive electrode sheet:

[0096] The active material (lithium cobalt oxide), binder (polyvinylidene fluoride), and conductive agent (conductive carbon black) were dissolved in an N-methylpyrrolidone solution at a weight ratio of 97:1.5:1.5 to form a positive electrode slurry with a solid content of 70%. Using aluminum foil as a current collector, the positive electrode slurry was coated onto the surface of the current collector to obtain the positive electrode active material layer.

[0097] A UV adhesive solution, composed of acrylates and a photoinitiator, is injected into an inkjet printer. The molar percentages of each component are: carbon-carbon double bonds in the acrylates: (2,4,6-trimethylbenzoyl)phosphine oxide: 2-isopropylthioxanthone = 92%: 4.5%: 3.5% (P and S elements have the same content). Then, a printing image file is created on a computer using drawing software according to the printing area size. The spray width is 6mm, and the width of the printing image file is also 6mm. Different K values ​​(i.e., relative contrast values, used to characterize color depth) are set for different areas of the printing image file according to the proportion of inactive substances sprayed. The P / S element mass percentage content is highest at the second end, which is 0.05%, meaning the P and S element mass percentage content at the second end is 0.05% higher than that in the uncoated area. The K value is set to 100%. The P / S element mass percentage content at the first end is... The mass percentage content of P and S elements is 0.02%, meaning that the mass percentage content of P and S elements at the second end is 0.02% higher than that of the uncoated area, which is 40% of the mass percentage content of P / S elements at the second end (0.02% / 0.05% = 40%). The K value is set to 40%. A gradient is set from the first end to the second end, so that the color of the inkjet image file changes from dark to light along the direction from the first coated area to the uncoated area. The drawn inkjet image file is imported into the inkjet printer. The spraying amount when the K value is set to 100% corresponds to a mass percentage content of 0.05% for P / S elements. The inkjet printer will automatically calculate the spraying amount for different areas based on the K value ratio (i.e., color depth) set for each area of ​​the image, and automatically calculate the spraying size according to the pattern size. Then, the inkjet printer is started, and the inkjet printer controls the operation of the corresponding printheads to spray the inactive substance paste onto the surface of the active substance layer according to the target spraying amount to form the first coated area. The UV adhesive is then cured by irradiation with a UV lamp. The resulting electrode sheet is cold-pressed and cut to obtain the positive electrode sheet. The P / S mass percentage content at the first end is 0.02%, and the P / S mass percentage content at the second end is 0.05%. The P / S mass percentage in the first coated area decreases from the second end to the first end, and the width of the first coated area is 6 mm. Since the positive electrode active material layer does not contain P or S elements, the P / S mass percentage content at the first end is 0.02% higher than that in the uncoated area, and the P / S mass percentage content at the second end is 0.05% higher than that in the uncoated area.

[0098] Preparation of the negative electrode sheet: A coating slurry was formed by mixing 80 wt% of an inorganic conductive agent (single-walled carbon nanotubes with a G / D ratio of 65), 10 wt% of a conductive polymer (polypyrrole), 10 wt% of a binder (5 wt% CMC-Li and 5 wt% PVDF), and an appropriate amount of water. Copper foil was used as the negative electrode current collector, and the coating slurry was applied to the surface of the current collector. After drying, a base coating with a thickness of 0.25 μm was obtained. A negative electrode slurry was formed by mixing 97.7 wt% graphite, 1.3 wt% sodium carboxymethyl cellulose, 1.0 wt% styrene-butadiene rubber, and an appropriate amount of deionized water. The negative electrode slurry was applied to the surface of the base coating, and after drying, a negative electrode active material layer was obtained. Subsequently, the negative electrode sheet was obtained through cold pressing and cutting.

[0099] Preparation of the separator membrane: Polyethylene film was selected as the separator membrane.

[0100] Preparation of electrolyte: Ethyl carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propylene propionate (PP), and vinylene carbonate (VC) were mixed in a weight ratio of 20:30:20:28:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 and the organic solvent were mixed in a weight ratio of 8:92 to obtain the electrolyte.

[0101] Preparation of lithium-ion batteries: The positive electrode, polyethylene separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes, and then wound to obtain an electrode assembly; the electrode assembly is placed in an aluminum-plastic film, and after liquid injection and formation, a lithium-ion battery is obtained.

[0102] Example 2-12

[0103] The difference from Example 1 lies in that at least one of the following is different: the mass percentage content of P and S at the first end of the first coated area, the mass percentage content of P and S at the second end of the first coated area, and the width of the first coated area. Specific parameters are shown in Table 1. In Table 1, the relative P / S content at the first end represents the difference between the mass percentage content of P / S at the first end and the mass percentage content of P / S in the uncoated area, and the relative P / S content at the second end represents the difference between the mass percentage content of P / S at the second end and the mass percentage content of P / S in the uncoated area.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that no inactive material slurry was coated on the surface of the positive electrode active material layer.

[0106] Comparative Example 2

[0107] The difference from Example 1 is that the mass percentage of P / S at each point in the first coating area is 0.05%.

[0108] Comparative Example 3

[0109] The difference from Example 1 is that the mass percentage of P / S at each point in the first coating area is 0.02%.

[0110] Comparative Example 4

[0111] The difference from Example 1 is that the mass percentage of P / S in the first coating area increases along the direction from the second end to the first end.

[0112] Lithium plating and energy density tests were performed on each embodiment and comparative example, and the test results are shown in Table 1.

[0113] Lithium deposition test on negative electrode:

[0114] At 25℃, the lithium-ion battery was charged to 4.30V with a constant current of X (X=1,2,3)C, then charged to 0.05C with a constant voltage of 4.30V, and left to stand for 5 minutes; then discharged to 2.0V with a constant current of 1C, and left to stand for 5 minutes. This constitutes one cycle, and is repeated 10 times. After this, the battery was disassembled in a fully charged state to obtain the negative electrode. If any area of ​​the negative electrode coating area opposite to the positive electrode coating area is found to be greater than or equal to 2mm... 2 Lithium deposition in certain areas is considered lithium deposition on the negative electrode, measured in carbon (C). A higher level of lithium deposition indicates a lower degree of deposition at the same charging rate.

[0115] Energy density test:

[0116] At 25°C, lithium-ion batteries (finished lithium-ion batteries after formation) are charged at a constant current of 1C to 4.35V, left to rest for 10 minutes, and then discharged at a constant current of 1C to the cutoff voltage of 3.0V (5 batteries per group) to obtain the energy of the lithium-ion battery. The energy density (Wh / L) of a lithium-ion battery = energy of the lithium-ion battery / volume of the lithium-ion battery.

[0117] Table 1

[0118]

[0119] As can be seen from Examples 1-15 and Comparative Examples 1-4, when the mass percentage content of P / S in the first coating area decreases along the direction from the second end to the first end, it has a higher level of lithium plating and a lower degree of lithium plating.

[0120] As can be seen from Examples 1-4 and 13-14, when the mass percentage content of P and S at the first end is 0.01% to 0.04% higher than that of the uncoated area, a better lithium plating effect is achieved. The smaller the mass percentage content of P and S at the first end, i.e., the closer it is to the mass percentage content of P and S in the uncoated area, the smoother the transition between the coated and uncoated areas, and the smaller the difference between the two, the higher the lithium plating level and the lower the degree of lithium plating. This is because the closer the mass percentage content of P and S at the first end is to that in the uncoated area, the lower the risk of kinetic abrupt changes at the boundary between the coated and uncoated areas, and the less lithium ions are concentrated at the abrupt change site. However, when the mass percentage content of P and S at the first end is too small compared to that in the uncoated area, the influence of inactive materials in this region is not significant, which is equivalent to narrowing the width of the inactive material coating area, and the improvement effect on lithium plating actually worsens.

[0121] As can be seen from Examples 1, 5-7, and 15, when the mass percentage content of P and S at the second end is 0.05% to 0.1% higher than that in the uncoated area, a better lithium plating effect is achieved. As the mass percentage content of P and S at the second end increases, the lithium plating level first increases and then decreases. This is because the higher the content of inactive materials, the more difficult it is for lithium ions to pass through this region. When the content exceeds a certain level, lithium ions cannot pass through this region and will bypass the region with the highest content of inactive materials (i.e., the region where the second end is located), resulting in lithium plating at the edge of the negative electrode corresponding to the second end of the positive electrode, thus reducing the overall lithium plating window of the battery. Furthermore, excessively high inactive material content affects the extraction of lithium ions from the positive electrode, significantly impacting the energy density of the lithium-ion battery.

[0122] As can be seen from Examples 1 and 8-12, when the width of the first coating area is 2 to 10 mm, it has a higher lithium plating level and a higher energy density; when the width of the first coating area is too large (greater than 10 mm), it has a greater impact on the energy density of the lithium-ion battery.

[0123] Example 16

[0124] The difference from Example 1 is that a PVDF adhesive is used to coat the surface of the active material layer to form a first coating area. The PVDF adhesive is formed by dissolving PVDF in N-methylpyrrolidone, and the concentration of PVDF in the PVDF adhesive is 5%. The mass percentage content of F at the first end is 0.2% higher than that in the uncoated area, and the mass percentage content of F at the second end is 0.5% higher than that in the uncoated area. The mass percentage content of F in the first coating area decreases from the second end to the first end, and the width of the first coating area is 6 mm.

[0125] Examples 17-21

[0126] The difference from Example 16 lies in that at least one of the following is different: the difference between the mass percentage content of F at the first end of the first coated region and the mass percentage content of F in the uncoated region, and the difference between the mass percentage content of F at the second end of the first coated region and the mass percentage content of F in the uncoated region. Specific parameters are shown in Table 2. In Table 2, the relative content of F at the first end represents the difference between the mass percentage content of F at the first end and the mass percentage content of F in the uncoated region, and the relative content of F at the second end represents the difference between the mass percentage content of F at the second end and the mass percentage content of F in the uncoated region.

[0127] Comparative Example 5

[0128] The difference from Example 16 is that the mass percentage of F at each point in the first coating area is 0.5%.

[0129] Comparative Example 6

[0130] The difference from Example 16 is that the mass percentage of F at each point in the first coating area is 0.2%.

[0131] Comparative Example 7

[0132] The difference from Example 16 is that the mass percentage of F in the first coating area increases along the direction from the second end to the first end.

[0133] Lithium plating and energy density tests were performed on each embodiment and comparative example, and the test results are shown in Table 2.

[0134] Table 2

[0135]

[0136] As can be seen from Examples 16-24 and Comparative Examples 5-7, when the mass percentage content of F in the first coating area decreases along the direction from the second end to the first end, it has a higher level of lithium plating and a lower degree of lithium plating.

[0137] As can be seen from Examples 16-18 and 22, when the mass percentage content of F at the first end is 0.2% to 0.4% higher than that of F in the uncoated area, a better lithium plating effect is achieved. The smaller the mass percentage content of F at the first end, i.e., the closer it is to the mass percentage content of F in the uncoated area, the smoother the transition between the coated and uncoated areas, and the smaller the difference between the two, the higher the lithium plating level and the lower the degree of lithium plating. This is because the closer the mass percentage content of F at the first end is to that of F in the uncoated area, the lower the risk of kinetic abrupt changes at the boundary between the coated and uncoated areas, thus avoiding the concentration of lithium ions at the abrupt change site. However, when the mass percentage content of F at the first end is too low compared to the mass percentage content of F in the uncoated area, the influence of inactive material in this region is not significant, which is equivalent to narrowing the width of the inactive material coating area, and the improvement effect on lithium plating actually worsens.

[0138] As can be seen from Examples 16, 19-21, and 23-24, a better lithium plating effect is achieved when the mass percentage content of F at the second end is 0.5% to 1% higher than that in the uncoated area. As the mass percentage content of F at the second end increases, the lithium plating level decreases. This is because the higher the content of inactive material, the more difficult it is for lithium ions to pass through this region. When the content exceeds a certain level, lithium ions cannot pass through this region and will bypass the region with the highest inactive material content (i.e., the region where the second end is located), resulting in lithium plating at the edge of the negative electrode corresponding to the second end of the positive electrode, thus reducing the overall lithium plating window of the battery. Furthermore, excessively high inactive material content affects the extraction of lithium ions from the positive electrode, significantly impacting the energy density of the lithium-ion battery.

[0139] Example 25

[0140] The difference from Example 16 is that a third coating area corresponding to the curved portion of the wound positive electrode sheet is formed on the surface of the active material layer using PVDF adhesive. Specifically, the mass percentage content of F at the center of the third coating area is 0.5% higher than that in the uncoated area, the mass percentage content of F at the edge of the third coating area is 0.2% higher than that in the uncoated area, the mass percentage content of F in the third coating area decreases from its center to its edge, and the width of the third coating area extending beyond the curved portion is 0 mm.

[0141] Examples 26-37

[0142] The difference from Example 25 lies in that at least one of the following is different: the difference between the mass percentage content of F at the center of the third coating area and the mass percentage content of F in the uncoated area, and the difference between the mass percentage content of F at the edge of the third coating area and the mass percentage content of F in the uncoated area. Specific parameters are shown in Table 3. In Table 2, the relative content of F at the center represents the difference between the mass percentage content of F at the center of the third coating area and the mass percentage content of F in the uncoated area, and the relative content at the edge represents the difference between the mass percentage content of F at the edge of the third coating area and the mass percentage content of F in the uncoated area.

[0143] Table 3

[0144]

[0145] As can be seen from Examples 25-39 and Comparative Example 8, when the percentage content of F in the third coating area decreases along the direction from its center to its edge, it has a higher level of lithium plating and a lower degree of lithium plating.

[0146] As can be seen from Examples 25-30 and 35-37, when the mass percentage content of F at the center of the third coating area is 0.5% to 1% higher than that of the uncoated area, and when the mass percentage content of F at the edge of the third coating area is 0.2% to 0.4% higher than that of the uncoated area, a better lithium plating effect is achieved.

[0147] As can be seen from Examples 31-34 and 38-39, when the width of the third coating area extending beyond the curved portion is 2 to 10 mm, it exhibits better lithium plating performance without significantly reducing the energy density.

[0148] The above-disclosed embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of this application. Therefore, any equivalent variations made in accordance with this application are still within the scope of this application.

Claims

1. A positive electrode plate, characterized in that, include: current collector; as well as An active material layer is disposed on the surface of the current collector. The active material layer includes a coated area and an uncoated area connected together. The coated area includes an inactive material, which is at least one of UV adhesive and PVDF. The inactive material can hinder the transport of metal ions. When viewed along the thickness direction of the positive electrode sheet, the coated area is located on at least one side of the uncoated area. The coated area includes a first coated area and a second coated area. Along the direction from the first coated area to the uncoated area, the content of the inactive material in the first coated area decreases. The second coated area is configured to correspond to the curved portion of the positive electrode sheet after winding. The content of the inactive material in the second coated area decreases along the direction from the center of the second coated area to the edge of the second coated area.

2. The positive electrode sheet as described in claim 1, characterized in that, The UV adhesive is formed by curing a UV adhesive liquid, which includes a resin and a photoinitiator.

3. The positive electrode sheet as described in claim 2, characterized in that, The resin comprises at least one of a polyacrylate prepolymer or a derivative thereof, and the photoinitiator comprises at least one of an acylphosphine oxide or a thioxanthone.

4. The positive electrode sheet as described in claim 1, characterized in that, The inactive substance contains at least one element selected from P, S, or F.

5. The positive electrode sheet as described in claim 4, characterized in that, The first coating area is configured to correspond to the edge of the active material layer. The first coating area includes a first end and a second end opposite to each other. The first end is connected to the uncoated area, and the second end is disposed away from the uncoated area. The mass percentage of P or S at the first end is 0.01% to 0.04% more than the mass percentage of P or S in the uncoated area, and the mass percentage of P or S at the second end is 0.05% to 0.1% more than the mass percentage of P or S in the uncoated area. The mass percentage of P or S at the first end is less than the mass percentage of P or S at the second end.

6. The positive electrode sheet as described in claim 4, characterized in that, The first coating area is configured to correspond to the edge of the active material layer. The first coating area includes a first end and a second end opposite to each other. The first end is connected to the uncoated area, and the second end is disposed away from the uncoated area. The mass percentage content of F at the first end is 0.2% to 0.4% more than the mass percentage content of F in the uncoated area, and the mass percentage content of F at the second end is 0.5% to 1% more than the mass percentage content of F in the uncoated area. The mass percentage content of F at the first end is less than the mass percentage content of F at the second end.

7. The positive electrode sheet as described in claim 1, characterized in that, The mass percentage content of F at the center of the second coated area is 0.5% to 1% higher than that of F in the uncoated area, the mass percentage content of F at the edge of the second coated area is 0.2% to 0.4% higher than that of F in the uncoated area, and the mass percentage content of F at the edge of the second coated area is less than that of F at the center of the second coated area; or, the mass percentage content of P or S at the center of the second coated area is 0.05% to 0.1% higher than that of P or S in the uncoated area, the mass percentage content of P or S at the edge of the second coated area is 0.01% to 0.04% higher than that of P or S in the uncoated area, and the mass percentage content of P or S at the edge of the second coated area is less than that of P or S at the center of the second coated area.

8. The positive electrode sheet as described in claim 1, characterized in that, The first coating area is configured to correspond to the edge of the active material layer, and the width of the first coating area is 2~10mm.

9. A method for preparing a positive electrode sheet as described in any one of claims 1-8, characterized in that, Includes the following steps: An active substance slurry is coated onto the surface of the current collector to form the active substance layer; An inactive substance slurry is coated onto the surface of the active substance layer to form the coating area, wherein when the first coating area is configured to correspond to the edge of the active substance layer, the coating weight of the inactive substance slurry decreases along the direction from the first coating area to the uncoated area; and when the second coating area is configured to correspond to the bend of the positive electrode sheet after winding, the coating weight of the inactive substance slurry decreases along the direction from the center of the second coating area to the edge of the coating area.

10. The preparation method according to claim 9, characterized in that, The step "coating the surface of the active material layer with an inactive substance slurry to form a coating area" includes: To create a printed image file, the maximum spraying amount is defined as the maximum content of inactive substances in the coated area. The relative contrast value of the printed image corresponding to the maximum spraying amount is 100%. Based on the maximum spraying amount, by setting the relative contrast value to decrease from the second end to the first end of the first coated area or from the center to the edge of the second coated area, the color of the printed image file correspondingly changes from dark to light along the direction from the first coated area to the uncoated area or from dark to light along the direction from the center of the second coated area to the edge of the second coated area. The inkjet image file is imported into the inkjet printing equipment, and the spraying amount is set when the relative contrast value is 100%. The inkjet printing equipment will set the corresponding spraying ratio according to the relative contrast value ratio of the image file, and spray the pattern of the corresponding size according to the size of the image file. The nozzle is controlled to spray an inactive substance slurry onto the surface of the active substance layer at a target spray volume to form the coating area.

11. The preparation method according to claim 9, characterized in that, The step "coating the surface of the active material layer with an inactive substance slurry to form a coating area" includes: To create an engraved pattern, the maximum coating amount is defined as the maximum content of inactive substances in the coating area. The relative contrast value of the image corresponding to the maximum coating amount is 100%. Based on the maximum coating amount, by setting the relative contrast value to decrease from the second end to the first end of the first coating area or from the center to the edge of the second coating area, the color of the engraved pattern changes from dark to light along the direction from the first coating area to the uncoated area or from dark to light along the direction from the center of the second coating area to the edge of the second coating area. The engraved pattern is imported into a gravure engraving machine, which engraves dot pits of different densities according to the relative contrast ratio of the engraved pattern to correspond to different coating amounts, thus producing a gravure roller. The inactive substance slurry is applied to the surface of the active substance layer using the gravure roller to form the coating area.

Citation Information

Patent Citations

  • Electrochemical device and electronic device

    CN116230940A

  • Pole piece, electrode assembly, battery monomer, battery and electric equipment

    CN219350608U